2011
DOI: 10.1371/journal.pone.0023933
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Novel Sphingosine-1-Phosphate Receptor Agonist W-061 in Murine DSS Colitis

Abstract: Although IL-17 is a pro-inflammatory cytokine reportedly involved in various autoimmune inflammatory disorders, its role remains unclear in murine models of colitis. Acute colitis was induced by 2.5% dextran sodium sulfate (DSS) treatment for 5 days. A novel sphingosine-1-phosphate receptor agonist W-061, a prototype of ONO-4641, was orally administered daily, and histopathological analysis was performed on the colon. The number of lymphocytes and their cytokine production were also evaluated in spleen, mesent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…In addition, we previously reported in the treatment of DSS for 5 days that Th17 cells significantly increased as early as on day 6 and then decreased on day 10, whereas Th1 cells significantly increased on day 10 with a delay in lamina propria (41). Therefore, we examined the influence of each ingredient on cytokine secretion of splenic mononuclear cells, which consist of macrophages, dendritic cells, and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we previously reported in the treatment of DSS for 5 days that Th17 cells significantly increased as early as on day 6 and then decreased on day 10, whereas Th1 cells significantly increased on day 10 with a delay in lamina propria (41). Therefore, we examined the influence of each ingredient on cytokine secretion of splenic mononuclear cells, which consist of macrophages, dendritic cells, and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the immunological aspects in IBD pathogenesis, we have recently shown that a new sphingosine 1-phosphate receptor agonist, W-061, ameliorated colitis induced by suppression of homing of T helper 17 (Th17) into lamina propria with dextran sulfate sodium (DSS) in wild-type mice, which are immunologically competent (41). In this experiment, we confirmed that Th17 and regulatory T cells (Tregs) in lamina propria had some important roles for the pathogenesis of colitis.…”
mentioning
confidence: 99%
“…In agreement, S1P is elevated during colitis and SphK1 expression is increased in patients with ulcerative colitis 26 . Several studies have also shown that FTY720 and other pharmacological agents that target S1PR1 are very effective in rodent models of colitis 78,110,111 , and several second-generation S1PR1 modulators are currently in clinical trials for patients with ulcerative colitis.…”
Section: Therapeutic Interventions In Inflammatory Disordersmentioning
confidence: 99%
“…Moreover, both KRP-203 and W-061 (another two S1P receptor agonists) were significantly effective in the treatment of chronic ongoing colitis in IL-10 -/-mice and DSS-induced acute colitis, respectively [22,23]. Compared with non-selective S1P receptor agonists, selective S1P1 agonists had the advantage of not inducing bradycardia, as type 3 S1P receptor (S1P3) was implicated directly in this complication [24].…”
Section: Cd62lmentioning
confidence: 99%